Evangelizing Congress: The Emergence of Evangelical Republicans and Party Polarization in Congress. Issue 3 (23rd March 2018) - Mathew, Nicole Asmussen
Abstract : The realignment of evangelical voters is well‐documented, but religion's impact within Congress is less clear. New data on home churches of members of Congress shows that the realignment of congressional evangelicals, combined with their growth and distinctly conservative legislative behavior, has significantly contributed to party polarization in Congress. Controlling for other factors, evangelicals are significantly more conservative than members of other religious traditions. This conservatism also has second‐order effects on the polarization of the House, where their more partisan proposals comprise a larger share of the roll‐call agenda when Republicans are in the majority. Moreover, evangelical Republicans in Congress differ significantly from evangelical Democrats in terms their geography, denominations, and experiences prior to Congress.